Update on ovulation-control programs for artificial insemination of lactating dairy cows - Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Use of timed AI programs has become commonplace on most dairy farms either because cows are not watched sufficiently to detect estrus, or because expression of estrus is limited by confinement housing. A number of programs are available to set up firstpostpartum inseminations that include some timed AI or timed AI of all cows once the end of voluntary waiting period (VWP) is reached. One approach may include a period of heat detection and AI until, for example, 100 days in milk, when a timed AI protocol is applied to all previously non-inseminated cows. Another approach includes injections of prostaglandin F2α, followed by periods of heat detection and AI, until a timed AI protocol is applied to all previously non-inseminated cows. Another approach may use a timed AI protocol that is applied so all cows can be first inseminated after the end of the VWP. The most sophisticated system involves presynchronizing estrous cycles during the latter part of the VWP and then applying a timed AI protocol. When protocols are applied correctly, ensuring that each cow is injected and inseminated appropriately, conception rates are either equal to, or slightly less, than those achieved when inseminations are based solely on behavioral signs of estrus (i.e., standing estrus). In contrast, pregnancy rates are almost always greater because more cows are inseminated (PR = AI submission rate × conception rate). Early application of Ovsynch before pregnancy status is known can allow all open cows to be re-inseminated by 2 to 3 days after their nonpregnant status is confirmed. This last program can essentially eliminate heat detection; when heats are observed, however, it becomes a bonus to the system.
Dairy Research, 2005 is known as Dairy Day, 2005
Keywords: Dairy; Ovulation control; Artificial insemination